Identification of Whitefly Species (Hemiptera: Aleyrodidae) Invaded Coconut Palms in Sri Lanka - Madushani, Manawaduge Ayesha; Sirisena, Anura Indrajith (Journal of Tropical Crop Science, 2024)
The current whitefly invasion is becoming a growing threat to coconut palms in Sri Lanka and will severely influence coconut production in the country. To effectively manage this problem, it is crucial toidentify the specific species that have invaded the coconut palms in the country to accordingly provide appropriate solutions. The taxonomy of the whitefly is mainly based on the characters of the pupae. Thus, a field survey was conducted in 2023 to identify the key whitefly species that invaded the coconut palms and their host range in Sri Lanka. The colonies of infested whiteflies were collected from coconut palms in different coconut-growing areas of Sri Lanka, and the pupae were slide-mounted and identified up to species level using taxonomic keys. Further, diagnostic characters of each species and host range were documented. The whitefly species found on the coconut palms (Cocos nucifera) were identified as Aleurodicus rugioperculatus, Aleurodicus dispersus, and Aleurotrachelus atratus. A. atratus was discovered only from the C. nucifera. A. dispersus and A. rugioperculatus were reported from 5 and 24 host plant species including the coconut from 5 and 18 different families respectively.